Evidence of gene deletion of p21 (WAF1/CIP1), a cyclin-dependent protein kinase inhibitor, in thyroid carcinomas. - Shi, Y. (Nature Publishing Group, 1996)
Eukaryotic cell cycle progression is controlled by a host of cyclin/cyclin-dependent kinases (Cdks), that are themselves regulated by multiple factors, including a group of small cyclin-Cdk inhibitor proteins (p15, p16, p21 and p27). The involvement of Cdk inhibitors in carcinogenesis has been demonstrated by the studies of p16. p53 is frequently mutated in thyroid carcinomas and p21/Waf1 is a downstream effector of p53. It is conceivable that genetic defects of genes downstream in the p53 pathway could also be oncogenic. We, therefore, examined a series of 57 thyroid tumour specimens (eight follicular adenomas and 49 carcinomas) for deletion and point mutation of the p21/Waf1 gene. Three different kinds of deletions ranging from 349 to 450 bp were detected in five papillary carcinoma specimens by reverse transcription-polymerase chain reaction (RT-PCR). All the deletions were involved in the second exon of the p21/Waf1 gene. RT-PCR single strand conformational polymorphism (SSCP) analysis of remaining samples failed to reveal any point mutations in the coding region of the gene, except for a polymorphism at codon 31 (Ser to Arg). Genomic Southern blot analysis did not demonstrate any gene deletion or rearrangement in these samples, indicating abnormal RNA splicing may be involved. Analysis of intron-exon boundary and the coding region of the second exon did not reveal any mutation except for a point mutation (C to G) located 16 bp downstream from the splice donor site of the second intron in three out of five samples with p21/Waf1 deletions. Whether the mutation plays any role in aberrant RNA splicing remains to be determined. Among the five samples with p21/Waf1 gene deletions, none of them simultaneously carried a p53 or retinoblastoma (Rb) gene mutation. No p21/Waf1 abnormality was found in the benign adenomas. Thus, 12.5% (5/40) of thyroid papillary carcinoma specimens harboured p21/Waf1 gene deletions. Our data suggest that p21/Waf1 gene deletion is involved in thyroid carcinogenesis and may play an important role in thyroid cell transformation. IMAGES: